Enhancing heart and circulatory well-being through optimized radial artery techniques: a meta-analysis of hemostasis and patient comfort - Yanru Yang; Hongyan Zhu; Guangyao Zai (Frontiers in Cardiovascular Medicine)
ObjectiveThis meta-analysis elucidates the efficacy of the Transradial Band Device (TR Band) in minimizing complications like radial artery occlusion and hematoma, preserving heart health, and enhancing blood flow post-transradial catheterization.MethodsA comprehensive literature search across databases including PubMed, Cochrane, and Embase examined the impact of radial artery compression techniques and decompression times on complications. Data from 13 studies were analyzed using R 4.1.2 with fixed-effects and random-effects models. The Newcastle-Ottawa Scale assessed the risk of bias in observational cohort studies.ResultsIn our meta-analysis, we evaluated data from various studies encompassing different air volumes in transradial band devices across several outcomes including bleeding, hematoma, radial artery occlusion (RAO), Visual Analog Scale (VAS) scores, and compression time. The collective analysis integrated findings from 11 studies, totaling 4,679 patients. No significant difference in bleeding risk (OR 1.04, 95% CI 0.60–1.82, p > 0.05, I2 = 78%), hematoma incidence (OR 0.96, 95% CI 0.78–1.19, p > 0.05, I2 = 0%), or RAO incidence (OR 0.96, 95% CI 0.78–1.19, p > 0.05, I2 = 0%) was observed between the “Less air” and “15 ml air” groups. However, the “Less air” group reported significantly higher VAS scores indicating increased pain or discomfort (Mean Difference 0.25, 95% CI 0.09–0.41, p < 0.05, I2 = 0%). Compression time analyses showed no significant difference between groups (Mean Difference −17.73, 95% CI −54.65–19.20, p > 0.05, I2 = 99%). Sensitivity analyses confirmed the stability of these findings, and Egger's test indicated no significant publication bias across the outcomes. This synthesis highlights the nuanced impact of air volume adjustments in transradial bands on patient outcomes, emphasizing the necessity for further research and standardized protocols to optimize patient safety and comfort post-intervention.ConclusionThe TR Band, when utilized with optimized air volume/pressure, maintains an essential balance between ensuring hemostasis and enhancing patient comfort without elevating the risk of radial artery complications. These findings support the careful selection of TR Band settings to optimize clinical outcomes in patients undergoing transradial cardiac procedures. Further research is warranted to establish standardized guidelines for the most effective use of TR Band in various clinical scenarios.